Community Development in Barak’s Slum Area Towards a Healthy and Livable Neighborhood in Kotabaru - Hanny Maria Caesarina; Cici Maryani Widayanti; Muhammad Rizqi Fatullah; Irfan Zamzani (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
The Kotabaru District Government has a plan to improve the slum area in the Barak area, Dirgahayu village, North Laut Island sub-district. This received pro and con reactions from the local community. This community service activity seeks to empower local communities in the Barak area about the importance of a healthy and livable residential environment. The methods used are observation, interviews and giving exposure to the Barak community to understand the current conditions of the Barak slum area and the responses of the people living in it. At the end of the activity, the percentage of people who rejected the plan to improve the quality of the Barak slum area dropped from 64% to 36%. Meanwhile, the percentage of people who agreed increased from 40% to 60% with the suggestion that improvement plans should pay attention to the social, cultural and economic aspects of the local community. In addition, the development plan for the relocation of the Barak slum area must pay attention to the balance between open space, built-up areas, and regional-scale public infrastructure.